R. MONEO - La vida de los edificios - Díez Medina, Carmen (ZARCH, 2019)
Rafael MoneoLa vida de los edificiosBarcelona: Acantilado, 2017, 220 páginas. Idioma: español. Tapa blanda. 16 €.ISBN-10: 8416748616; ISBN-13: 978-8416748617